2022
DOI: 10.3389/fmars.2022.782680
|View full text |Cite
|
Sign up to set email alerts
|

Low Survivals and Rapid Demographic Decline of a Threatened Estuarine Delphinid

Abstract: Beibu Gulf’s (BBG) Indo-Pacific humpback dolphins present both a genetic differentiation and phenotypical differences from conspecifics from other areas of the South China Sea. Given the recent urbanization and industrialization in southern China, humpback dolphins from the BBG warrant conservation attention. However, this population’s demographic trend is unclear, making it hard to take conservation measures. To assess the population status of humpback dolphins in the BBG, photo-identification surveys were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…In addition, we failed to match this individual to the existing photo-identification catalogues of populations from the Xiamen Bay, Lingding Bay, Leizhou Peninsula, Sanniang Cove and west Hainan populations (Wang et al ., 2016; Tang et al ., 2021). Therefore, this individual was unlikely a migrant from one of the currently known populations from the south China waters (Lin et al ., 2022). On the other hand, the presently reported sighting was very close (<50 km) to the location of the by-catch reported in 2003 (Figure 1B, Han et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we failed to match this individual to the existing photo-identification catalogues of populations from the Xiamen Bay, Lingding Bay, Leizhou Peninsula, Sanniang Cove and west Hainan populations (Wang et al ., 2016; Tang et al ., 2021). Therefore, this individual was unlikely a migrant from one of the currently known populations from the south China waters (Lin et al ., 2022). On the other hand, the presently reported sighting was very close (<50 km) to the location of the by-catch reported in 2003 (Figure 1B, Han et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the information gathered on these animals' dispersing distance, we suggest that this individual may not come from one of the known populations of the East China Sea or the South China Sea, but from a previously undescribed population in the Yellow Sea. The putative population may be one of the relict populations of species surviving the Last Glacial period (Lin et al, 2010), which were generally very small in their population sizes (as the one in the Ningde waters which is <20 individuals) and highly susceptible to human development (Lin et al, 2016(Lin et al, , 2022). An area, the Yalu River mouth, which is the largest river mouth and most likely the least disturbed area of the region, could be the most suitable niche of the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross‐comparisons found no matching individuals in any pair of regions (Figure 2b). The survey effort in the PRE and SNB (2,458 and 158 identified individuals, respectively) was sufficient to capture the majority of the population in each of these two regions (Chen et al, 2010a; Chen et al, 2011b; Chen et al, 2016; Peng et al, 2020; Lin et al, 2022b). In contrast, the numbers of identified individuals in the SWH (169) and EZJ (373) were not considered fully representative of the population sizes (Xu et al, 2012; Xu et al, 2015; Liu et al, 2022) because the discovery curves depicting the cumulative number of identified individuals were still rising (Tang et al, 2021).…”
Section: Photo‐identification Cross‐matching: Low Inter‐population Co...mentioning
confidence: 99%
“…Since the skin color pattern of IPHDs is associated with age (Jefferson, 2000;Jefferson, et al, 2012), photo-identification analyses provide information on population age-class structure. In contrast, the sex of the dolphins is difficult to obtain, and several studies that attempted to describe social structure, and estimate reproductive success or survival of IPHDs highlighted the need to determine the sex of more individuals (e.g., Dungan et al, 2012Dungan et al, , 2016Guo et al, 2020;Lin et al, 2022;Zeng et al, 2021). The possibility to determine the sex of these animals, using photographs, has been tested by Wright et al (2017), with the study being focused on healing time and sex differences in two populations.…”
mentioning
confidence: 99%